Relationship between Chlamydia trachomatis and Mycoplasma genitalium infection and pregnancy rate and outcome in Iranian infertile couples. (29th December 2016) - Dehghan Marvast, L.; Aflatoonian, A.; Talebi, A. R.; Eley, A.; Pacey, A. A.
Summary: The study was performed to investigate the prevalence of Chlamydia trachomatis and Mycoplasma genitalium in a population of infertile couples from Iran and how this relates to tubal factor infertility, pregnancy rate and outcome of pregnancy. Blood, semen and first‐void urine samples were obtained from 250 infertile couples and 250 fertile women as a control. Infertile couples were followed up after 24 months to determine diagnosis, referral for assisted conception, any pregnancy and pregnancy outcome. Data were analysed with regard to the results of (i) serological analysis for specific antibodies to C. trachomatis in serum; (ii) the presence of C. trachomatis and M. genitalium DNA in first‐void urine; and (iii) in a semen sample of the male partner. Prevalence of C. trachomatis in our study population was comparable to other studies using similar methods and test specimens. No evidence of M. genitalium infection was found. Detection of C. trachomatis in one partner rarely correlated with infection in the other. The risk of tubal factor infertility and the probability of pregnancy and pregnancy outcome were unrelated to the results of serological tests for C. trachomatis antibodies or the presence of C. trachomatis DNA in first‐void urine of both partners and in a semen sample provided by the male.